Pengaruh Lingkungan Eksternal Dan Lingkungan Internal Terhadap Kinerja Ukm Melalui Keunggulan Bersaing Pada UKM Di Kota Sorong - Tutri Hanggari Citra Rini; Muhammad Irhas Effendi; Haddy Suprapto (Jurnal Ilmu Administrasi dan Bisnis, 2021)
This study aims to determine and analyze the influence of the external environment and the internal environment on the performance of SMEs through competitive advantage in SMEs in Sorong City - West Papua. The population in this study were SMEs in Sorong City which included food and beverage, metal and service industries, forest products and furniture, building materials, and handicrafts totaling 539 SMEs, and the samples in this study were 135 SMEs. sampling using proportional cluster random sampling. Data analysis methods include descriptive analysis and quantitative analysis with analysis tools using SEM (Structural Equation Modeling) and AMOS (Analysis Moment of Structural) programs. The findings of this study are  the external environment is proven to have a negative and significant effect on the performance of SMEs; the external environment is proven to have a negative and significant effect on SME performance mediated by competitive advantage; the internal environment is proven to have a positive and significant effect on the performance of SMEs; the internal environment is proven to have a positive and significant effect on SME performance mediated by competitive advantage. Keywords: external environment, internal environment, competitive advantage, performance of SMEs.